Restoring Dignity: Rehabilitation of Disabled Veterans of the Indonesian war of Independence (1946-1977) - Ratih Lutfita Ningtyas; Carmia Annafi; Wilda Nur Afiah (UIN Imam Bonjol Padang, 2025)
This research aims to analyze rehabilitation efforts for disabled veterans as a form of restoring their dignity in medical, social and economic aspects. The study was conducted using the historical method which includes heuristic, criticism, interpretation and historiography. Historical sources used were Rehabilitation Centrum archives, Soeharso doctor reports, and contemporaneous newspapers reporting on RC. According to the results of the research, the Government through the Rehabilitation Centrum (RC) Surakarta, seeks to honor the services of heroes and restore the dignity of disabled veterans through medical rehabilitation, fitting of prostheses, and providing vocational training to increase the social independence and economic independence of veterans. After participating in rehabilitation and returning to the community, disabled veterans can be channeled into various jobs or entrepreneurship.